Case Report: Diagnosis of Acute Q Fever With Aseptic Meningitis in a Patient by Using Metagenomic Next-Generation Sequencing - Gu, Meifeng; Mo, Xiaoqin; Tang, Zhenchu; Tang, Jianguang; Wang, Wei (Frontiers in Medicine, 2022)
Query fever (Q fever) is a widespread zoonotic disease caused by the bacterium of Coxiella burnetii. Its neurological complications are rarely reported. But they may lead to severe consequences. It needs a rapid and accurate detective method to diagnose acute Q fever with neurological presentations in non-epidemic areas urgently. Here, we report an acute Q fever case with aseptic meningitis. The male patient, without any contact history in the epidemic area or with animals, was indicated to exhibit fever and headache symptoms. The cultures of blood, stool, urine, and sputum were all negative. But Coxiella burnetii was repeatedly detected in blood by metagenomic next-generation sequencing (mNGS). He received Doxycycline therapy and quickly returned to normal. Therefore, for the diagnosis and identification of Q fever in non-reporting regions, mNGS has comparative advantages. Secondly, aseptic meningitis may be a direct infection of C. burnetii to central nervous system (CNS) or inflammatory reactions to systemic infection, we recommend detecting mNGS both in blood and cerebrospinal fluid (CSF).